The combination of left ventricular non-compaction and hypertrophic cardiomyopathy in one family with a pathogenic variant in the MYBPC3 gene (rs397516037) - R. P. Myasnikov; A. V. Kulikova; A. N. Meshkov; E. A. Mershina; A. V. Kiseleva; M. V. Klimushina; M. G. Divashuk; O. V. Kurilova; P. S. Pilyus; M. S. Kharlap; S. N. Koretsky; O. M. Larina; et al. (Российский кардиологический журнал, 2020)
The article presents the results of clinical, instrumental and molecular genetic tests of three generations of a family with inherited cardiomyopathy caused by a new variant in the MYBPC3 gene. A specific feature of this case is the phenotypic heterogeneity of the mutation — a combination of hypertrophic cardiomyopathy and left ventricular non-compaction in family members. Attention is drawn to the various severity of clinical manifestations in relatives of carriers of mutation: from asymptomatic to severe heart failure and acute cerebrovascular accident.